2023
DOI: 10.3390/polym15020261
|View full text |Cite
|
Sign up to set email alerts
|

Blending of Low-Density Polyethylene and Poly(Butylene Succinate) (LDPE/PBS) with Polyethylene–Graft–Maleic Anhydride (PE–g–MA) as a Compatibilizer on the Phase Morphology, Mechanical and Thermal Properties

Abstract: It is of significant concern that the buildup of non-biodegradable plastic waste in the environment may result in long-term issues with the environment, the economy and waste management. In this study, low-density polyethylene (LDPE) was compounded with different contents of poly(butylene succinate) (PBS) at 10–50 wt.%, to evaluate the potential of replacing commercial plastics with a biodegradable renewable polymer, PBS for packaging applications. The morphological, mechanical and thermal properties of the LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…These natural fibers are nontoxic, biodegradable, readily available, and light in weight. , As a result, they are widely used to create polymer composites that are reinforced with fiber. Natural fibers like jute, cotton, hemp, sisal, date palm leaf coir, flax, sawdust, and rice husk are frequently used in polymer composites. , Natural fibers are a great alternative to synthetic reinforcements because of their widespread availability and flexibility in improving their qualities via surface treatments. These composites are used in the construction and automotive industries. ,,, Several studies reported using a variety of thermoplastic polymers for reinforcing natural fiber using polypropylene, santoprene, low-density polyethylene (LDPE), HDPE, and polyvinyl chloride. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These natural fibers are nontoxic, biodegradable, readily available, and light in weight. , As a result, they are widely used to create polymer composites that are reinforced with fiber. Natural fibers like jute, cotton, hemp, sisal, date palm leaf coir, flax, sawdust, and rice husk are frequently used in polymer composites. , Natural fibers are a great alternative to synthetic reinforcements because of their widespread availability and flexibility in improving their qualities via surface treatments. These composites are used in the construction and automotive industries. ,,, Several studies reported using a variety of thermoplastic polymers for reinforcing natural fiber using polypropylene, santoprene, low-density polyethylene (LDPE), HDPE, and polyvinyl chloride. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…1,3,6,19 Several studies reported using a variety of thermoplastic polymers for reinforcing natural fiber using polypropylene, santoprene, low-density polyethylene (LDPE), HDPE, and polyvinyl chloride. 1,2,20,21 Automotive manufacturers are increasing demand for natural polymer composites that can minimize pollution while still being lighter and more fuel efficient. 3−5 Natural fibers are more shatter resistant than glass fiber composites, have enhanced energy management capabilities, and have higher sound absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agglomerates are characterized by: distinct phase morphologies, coalescence, and poor mechanical properties. Two strategies emerged to ensure compatibility: ZnO surface modification with non-polar substances like oleic acid [ 33 ] or adding a compatibilizer to the LDPE, like low-density polyethylene grafted with maleic anhydride (LDPE-g-MA) [ 34 , 35 , 36 ]. The compatibilizer will reduce the interfacial tension and improve the adhesion between the composites’ phases.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the interfacial adhesion problem in composites, it is common to perform treatments on natural fibers in order to modify their surfaces and improve compatibility with the polymer matrix. Among the various methods used, compatibilization stands out, with maleic anhydride compatibilization being widely employed in this context [25,26]. Maleic anhydride acts as a coupling agent, reacting with the hydroxyl groups present in natural fibers and forming chemical bonds with the polymer of the matrix [27].…”
Section: Introductionmentioning
confidence: 99%